2019
DOI: 10.1029/2019gl085167
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Fracture Injection Strategy Influences the Probability of Earthquakes in the Eagle Ford Shale Play of South Texas

Abstract: Seismicity in the Eagle Ford play grew to 33 times the background rate in 2018. We identified how hydraulic fracturing (HF) contributed to seismicity since 2014 by comparing times and locations of HF with a catalog of seismicity extended with template matching. We found 94 ML ≥ 2.0 earthquakes spatiotemporally correlated to 211 HF well laterals. Injected volume and number of laterals on a pad influence the probability of seismicity, but effective injection rate has the strongest effect. Simultaneous stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 67 publications
7
61
0
Order By: Relevance
“…Inset shows cumulative number of earthquakes ( M ≥ 3.0) for this area from the USGS Comprehensive Catalog. Figure modified from Fasola et al (2019).…”
Section: Summary Of Documented Casesmentioning
confidence: 99%
“…Inset shows cumulative number of earthquakes ( M ≥ 3.0) for this area from the USGS Comprehensive Catalog. Figure modified from Fasola et al (2019).…”
Section: Summary Of Documented Casesmentioning
confidence: 99%
“…In the mid-continental USA, we use the clusters of HF-IS identified by Yoon et al (2017) from stimulation of the Fayetteville Shale in Arkansas in 2010, where magnitudes reached M 2.9. To these, we add the 2011 sequence from Garvin County, OK, where magnitudes again reached M 2.9 (Holland, 2013); the 2014 sequence from Carter County, OK, where magnitudes reached M 3.2 (Darold et al 2014), and the 2018 M 3.5 sequence near to Karnes City, TX (Fasola et al, 2019). In the Appalachian Basin, we consider the 2013 Harrison County sequence identified by Friberg et al (2014), and the Mahoning County sequence identified by Skoumal et al (2015), both of which were associated with stimulation of the Utica Shale.…”
Section: United Statesmentioning
confidence: 99%
“…We use the Kolmogorov-Smirnov test, with a 20% significance threshold (Clauset et al, 2009) to determine M MIN , requiring at least 30 events larger than this magnitude. This limits our analysis to the 3 UK Bowland Shale cases; the Crooked Lake clusters 1, 2, 3, and 6 (Bao and Eaton, 2016); Tony Creek (Eaton et al, 2018); the Red Deer ESB02 and ESB10 clusters (Schultz and Wang, 2020); the 2015 Montney sequence described by Babaie Mahani et al (2017); the Septimus sequence described by Peña-Castro et al (2020); Garvin County, OK (Holland, 2013); Karnes City (Fasola et al, 2019); and the Guy-Greenbrier clusters (Yoon et al, 2017).…”
Section: Next Record-breaking Event Magnitudesmentioning
confidence: 99%
See 2 more Smart Citations